Second (monetary) pillar of the European Central Bank’s monetary policy – history of its genesis, characteristics and its relevance to the ECB’ s monetary policy - Duvačová, Katarína; Kollár, Miroslav; Chytilvá, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2008)
Abstract Monetary policy of the ECB was created under the conditions of extreme uncertainty. This was probably one of those reasons, why Otmar Issing – the mastermind of monetary pillar of ECB´s monetary strategy decided not to go the conventional way. His decision and the key principle of the monetary pillar – to give the money a prominent role - faced and still face the criticism. Nevertheless, the monetary policy of the ECB works quite successfully more than eight years after the implementation of the two pillars approach. Thanks to the stable price level, the ECB is these days one of the most credible institution in the world. If the credibility of the ECB is also a merit of the monetary pillar, how the monetary pillar was created, how it works, its contribution to the price stability in the Euro zone, and if implementation of this pillar was a right decision – this all is going to be discussed in this bachelor paper. Key words: monetary policy, price level, central bank, monetary aggregate JEL Classification: E520, E580, E310 Abstrakt Měnová politika Evropské centrální banky byla vytvořena za velmi nejistých podmínek. To byl pravděpodobně jeden z hlavních důvodů, proč se Otmar Issing, mentor měnového pilíře, rozhodl pro netradiční strategii měnové politiky pro nadcházející měnovou unii. Jeho rozhodnutí a zároveň základní princip měnového pilíře – prominentní role peněz čelí neustále kritice. Měnová politika ECB navzdory kritice splňuje stanovený cíl cenové stability už více než osm let a vzhledem k tomu je nyní jednou z nejdůvěryhodnějších institucí. Zásluha měnového pilíře v dosáhnutí zmíněné dlouhodobé cenové stability je však téma k diskuzi. Historie měnového pilíře, jeho fungování, charakteristika a zejména relevance pro měnovou politiku ECB je předmětem této bakalářské práce. Klíčová slova: měnová politika, cenová hladina, centrální banka, měnový
Vedoucí práce: Miroslav Kollár
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2008
Rok obhajoby 2008
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses